(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
The functioning of Doshas commences at the very onset of life, specifically at the moment of conception. The balance of these three Doshas, integral to one’s Prakriti, has the potential to interfere with the typical physiological processes in humans. Doshas and Dhatus exhibit a relationship characterized by Ashrya-Ashrayee Bhava. Each Dhatu is also associated with an Updhatu. Stanya and Raja are recognized as Updhatus of Rasa Dhatu. Since Stanya is an Updhatu of Rasa Dhatu, the factors that promote the formation of Rasa Dhatu will similarly enhance the development of Stanya Updhatu, and conversely. The determination of an individual’s Prakriti is based on the predominance of Doshas. Consequently, the current research seeks to establish a connection between Daihik Prakriti and the components of Stanya. Methods: This observational study done for biochemical analysis of Stanya and its correlation with Daihik Prakriti.. For this, 50 healthy lactating mothers were selected as subjects and their Prakriti were determined by using standard CCRAS performa. Breast milk were assessed for the different constituents in research laboratory and were compared later with Prakriti. Every sample of Stanya was examined by Jala Pariksha. Results: The result obtained shows that there is no significant correlation between Prakriti and fat, protein, SNF, lactose % levels, significant positive correlation between density and water % level with Prakriti, significant positive correlation was found on Jal Pariksha between color and appearance with different Prakriti and negative significant correlation between consistency and dissolution in water with Prakriti. Conclusion: The results of biochemical analysis of milk for the attributes like density, Consistency, water percentage, color and Jal Pariksha have been in consistency with the properties mentioned by our Acharyas w.s.r to Vata, Pitta and Kapha Pradhan dosha thus inferring that the Prakriti has direct impact on the properties of Stanya.